2017
DOI: 10.2337/db17-0194
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Methyltransferase MLL1 Directs Macrophage-Mediated Inflammation in Wound Healing and Is Altered in a Murine Model of Obesity and Type 2 Diabetes

Abstract: Macrophages are critical for the initiation and resolution of the inflammatory phase of wound repair. In diabetes, macrophages display a prolonged inflammatory phenotype in late wound healing. Mixed-lineage leukemia-1 (MLL1) has been shown to direct gene expression by regulating nuclear factor-κB (NF-κB)–mediated inflammatory gene transcription. Thus, we hypothesized that MLL1 influences macrophage-mediated inflammation in wound repair. We used a myeloid-specific Mll1 knockout (Mll1f/fLyz2Cre+) to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 48 publications
4
74
0
Order By: Relevance
“…This switch is significantly impaired in obesity/T2D and results in chronic inflammation and nonhealing wounds; however, the etiology is unclear. We and others have previously identified that chronic inflammation in diabetic wounds is governed by epigenetic regulation of macrophages (12)(13)(14)(15)(16). In this study, we identify that the HAT MOF regulates inflammation in macrophages during normal and diabetic wound repair.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…This switch is significantly impaired in obesity/T2D and results in chronic inflammation and nonhealing wounds; however, the etiology is unclear. We and others have previously identified that chronic inflammation in diabetic wounds is governed by epigenetic regulation of macrophages (12)(13)(14)(15)(16). In this study, we identify that the HAT MOF regulates inflammation in macrophages during normal and diabetic wound repair.…”
Section: Discussionsupporting
confidence: 49%
“…Sustained inflammation due to the inability of wound macrophages to transition to the regeneration stage necessary for normal skin repair is a hallmark of impaired wound healing associated with diseases such as type 2 diabetes (T2D) (6)(7)(8)(9)(10)(11). The mechanisms regulating this failed macrophage transition are not completely clear, but recent evidence suggests that epigenetic signatures can drive prolonged inflammation in diabetic wounds (12)(13)(14)(15)(16). Our group and others have identified that diabetic wound macrophages exhibit changes in histone methylation that promote a proinflammatory phenotype (12,14,16).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We used a gating strategy selecting live, lineage − (CD3 − , CD19 − Ter119 − , NK1.1 − ), nonneutrophil (Ly6G − ), CD11b + cells, as previously described ( Fig. 2A) [29,30]. It has been previously documented by our group and others that Ly6C Hi demonstrate a proinflammatory phenotype, whereas Ly6C Lo cells demonstrate a reparative phenotype [8,13,[31][32][33].…”
Section: Loss Of Ccr2 In Wound Macrophages Results In Decreased Inflamentioning
confidence: 99%
“…JMJD3, a major regulator of macrophage activation, has been involved in type‐II diabetes, by driving pro‐inflammatory IL‐ 12 production in murine macrophages (Gallagher et al, ). Furthermore, monocytes from type‐II diabetic patients exhibit increased MLL1 methyltransferase compared to healthy controls (Kimball et al, ). In psoriasis patients, mRNA of Ezh2 and Suv39h1 methyltransferases were found increased, however, no significant differences in H3K27 and H3K4 global methylation pattern was observed (Zhang et al, ).…”
Section: Contribution Of Histone Modifying Enzymes In Inflammatory DImentioning
confidence: 99%